Full‐core coupled neutronic/thermal‐hydraulic modelling of the EBR‐II SHRT‐45R transient. (27th June 2016) - Caron, D.; Bonifetto, R.; Dulla, S.; Mascolino, V.; Ravetto, P.; Savoldi, L.; Valerio, D.; Zanino, R.
Summary: During the last decade the European activities in the field of nuclear fission research include the design of fast reactors cooled by liquid metals. Within this framework, the Fast REactor NEutronics/Thermal‐hydraulICs (FRENETIC) code is being developed at Politecnico di Torino over the last few years. It implements a full‐core coupled neutronic/thermal‐hydraulic model of a liquid‐metal‐cooled fast reactor as relevant for two of the six options currently under study within the framework of the Generation‐IV International Forum, namely the lead‐cooled fast reactors and the sodium‐cooled fast reactors. The code validation process involves the participation in a coordinated research project of the International Atomic Energy Agency, aiming at testing different computational tools against the shutdown heat removal tests performed many years ago in the sodium‐cooled Experimental Breeder Reactor‐II (EBR‐II) at Argonne National Laboratory, USA. In this paper, results of the FRENETIC analysis of one of the transients considered in the project, the unprotected EBR‐II shutdown heat removal test SHRT‐45R, are presented and compared to the measurements, providing the first validation of the coupled neutronic/thermal‐hydraulic features of the FRENETIC code. Copyright © 2016 John Wiley & Sons, Ltd.